A new method of "student-centered formative assessment" and improving students' performance: An effort in the health promotion of community - Fateme Shahedi; Javad Ahmadi; Tahereh Sharifi; Seyedeh Nahid Seyedhasani; Mahbubeh Abdollahi; Negar Shaabani; Mohammad Sarmadi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Improving the learning process in education will empower medical students, and also formative assessment helps improve the teaching-learning process by providing ongoing reflective information about learning gaps. OBJECTIVE: The aim of this study was to explore the effect of student-centered formative assessment by weekly reflective self-correction quizzes on medical laboratory students' performance on the final examination of hematology course in 2018. MATERIALS AND METHODS: A semi-experimental study was conducted on fifty students divided randomly into intervention (n = 25) and control groups (n = 25) using convenience sampling in 2018 from Torbat Heydariyeh University of Medical Sciences, Iran. Data analysis was performed using SPSS software version 16, two-sample t- test, Chi-square test, and analysis of covariance. RESULTS: The intervention had positive effects on students' mean test scores in hematology II so that the intervention and control groups managed to obtain 18.45 ± 1.46 and 14.57 ± 2.64, respectively (P < 0.01). CONCLUSIONS: The results suggested that weekly formative assessments along with reflective self-correction activity and active participation of students in the learning process by designing questions could improve student learning.